2018
DOI: 10.2174/1389200219666180330125003
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Hepatoprotective Effect of Herbalism Against Ethanol Induced Hepatotoxicity: A Review

Abstract: Accordingly, this review provides several evidences which show that these medicinal plants could be used for the treatment and prevention of ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, it is greatly significant to investigate the pathogenesis of alcoholic liver disease and develop effective treatment medicine in the treatment and prevention of alcoholic liver disease. Recently, herbal medicines have attracted increasing attention in the treatment of alcoholic liver injury, due to the wide availabilities, multitarget actions, and low side effects [ 14 16 ]. Chinese herbal medicines of saponins from the leaves of Panax notoginseng , Camellia nitidissima, and phenol have been used to improve the alcohol-induced liver injury [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is greatly significant to investigate the pathogenesis of alcoholic liver disease and develop effective treatment medicine in the treatment and prevention of alcoholic liver disease. Recently, herbal medicines have attracted increasing attention in the treatment of alcoholic liver injury, due to the wide availabilities, multitarget actions, and low side effects [ 14 16 ]. Chinese herbal medicines of saponins from the leaves of Panax notoginseng , Camellia nitidissima, and phenol have been used to improve the alcohol-induced liver injury [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that S. miltiorrhiza can inhibit hepatic stellate cell activity by enhancing natural killer cell functions to block liver fibrosis (82). Moreover, TCMs can protect the liver and reduce liver fibrosis by improving inflammation and reducing steatosis (83).…”
Section: Treatment Of Liver Fibrosis With Tcmmentioning
confidence: 99%
“…Plowes, Geranium schiedeanum Schltdl., and Phyllanthus emblica L. are also effective in this respect (Ibrahim et al, 2015;Madrigal-Santillán et al, 2015;Chaphalkar et al, 2017). Recently a number of reviews have been published on the topic (Guan et al, 2018;Singh et al, 2018).…”
Section: Preclinical and Clinical Research Based On Ethnopharmacologimentioning
confidence: 99%